2009
DOI: 10.4049/jimmunol.0803362
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Experimental Autoimmune Encephalomyelitis by Ghrelin

Abstract: Ghrelin is a recently identified gastric hormone that displays strong growth hormone-releasing activity mediated by the growth hormone secretagogue receptor. While this unique endogenous peptide participates in the regulation of energy homeostasis, increases food intake, and decreases energy expenditure, its ability to inhibit the production of proinflammatory cytokines in vitro indicates its role in the regulation of inflammatory process in vivo. Here we examine the effect of exogenous ghrelin on the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 40 publications
(41 reference statements)
2
57
0
1
Order By: Relevance
“…Furthermore, in mouse experimental autoimmune encephalomyelitis, a model of multiple sclerosis, sc ghrelin administration was followed by a reduced clinical severity of the disease. This effect was coupled with reduced mRNA levels of proinflammatory cytokines (TNF-a, IL1b, IL-6) in the spinal cord cellular infiltrates and microglia (Theil et al 2009). In addition, the ability of ghrelin to decrease the presence and the activation of encephalitogenic T helper 1 (Th1) and Th17 cells in periphery and nervous system and to induce regulatory T cells reinforces the idea of ghrelin as a promising agent to arrest or slow the progression of this disease (Souza-Moreira et al 2013).…”
Section: Multiple Sclerosismentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, in mouse experimental autoimmune encephalomyelitis, a model of multiple sclerosis, sc ghrelin administration was followed by a reduced clinical severity of the disease. This effect was coupled with reduced mRNA levels of proinflammatory cytokines (TNF-a, IL1b, IL-6) in the spinal cord cellular infiltrates and microglia (Theil et al 2009). In addition, the ability of ghrelin to decrease the presence and the activation of encephalitogenic T helper 1 (Th1) and Th17 cells in periphery and nervous system and to induce regulatory T cells reinforces the idea of ghrelin as a promising agent to arrest or slow the progression of this disease (Souza-Moreira et al 2013).…”
Section: Multiple Sclerosismentioning
confidence: 97%
“…Macrophage lineage, activated endothelium, human lymphocytes and thymus express several somatostatin receptor subtypes and the MrgX2 receptor (van Hagen et al 2008), suggesting that cortistatin might represent the link between ghrelin and the somatostatin/ cortistatin system in the immune system. Ghrelin, Unacylated Ghrelin, and Obestatin Secretion and Activity in Acute and Chronic Inflammatory States Several studies on the anti-inflammatory activity of ghrelin showed that only the acylated peptide was able to decrease the expression and production of proinflammatory cytokines: interleukin (IL)-1a, IL-1b, IL-6, and tumor necrosis factor (TNF)-a by activated T cells and by lipopolysaccharide (LPS)-activated monocytes and microglia (Dixit et al 2004;Li et al 2004;Theil et al 2009). Ghrelin has been shown to prevent also microglial activation in a mouse model of Parkinson's disease by inhibiting the expression of TNF-a and IL-1b induced by administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and to prevent the release of TNF-a and IL-1b from microglia treated with threohydroxyaspartate (Lee et al 2012;Moon et al 2009).…”
Section: Ghrelin and Ghs-r1a Mrna Expression And Distribution In The mentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin administration attenuated anorexia as well as inflammation and rate of mortality during endotoxin-or IL-1 -induced inflammation (Chang et al, 2003;Wu et al, 2007;Chorny et al, 2008). In chronic inflammation, treatment with ghrelin significantly ameliorated experimental colitis in mice and rats (Gonzalez-Rey et al, 2006;Konturek et al, 2009), chronic kidney disease in rats (Deboer et al, 2008) or experimental autoimmune encephalomyelitis in mice (Theil et al, 2009) due to its inhibitory effect on pro-inflammatory cytokines. In experimental arthritis in rats, ghrelin treatment significantly reduced clinical signs of the disease as well as the release of the high mobility box 1 (HMGB1), a DNA-binding factor that acts as a late inflammatory factor (Chorny et al, 2008).…”
Section: Anorexia and Starvation In Inflammatory Diseasesmentioning
confidence: 99%
“…Devido à inacessibilidade do SNC dos pacientes e a similaridade do modelo quanto à patogênese de autoimunidade, inflamação do SNC, desmielinização e sintomas (BAXTER, 2007;SOSPEDRA;, atualmente o modelo de EAE é responsável por cerca de 9.300 trabalhos publicados no PubMed e vem se mostrando importante para o estudo de diversas substâncias antiinflamatórias permitindo a translação dos resultados para humanos (ELLOSO et al, 2005;GREENWOOD et al, 2006;THEIL et al, 2009). A EAE é mais comumente induzida em camundongos, mas pode também ser induzida em outras espécies como ratos, coelhos e macacos.…”
Section: Figura 1 -Representação Esquemática Da Evolução Clínica Da Emunclassified